PENGARUH GAYA KEPEMIMPINAN KEPALA SKB, MOTIVASI KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA PAMONG BELAJAR PADA SANGGAR KEGIATAN BELAJAR (SKB) DI WILAYAH PRIANGAN JAWA BARAT - LILI DASA PUTRI (Departemen Pendidikan Luar Sekolah FIP, 2016)
Influence of Leadership Style Head of SKB, work motivation and performance in the Civil Learning SKB (SKB) in the Priangan region of West Java. The background of this research is to the performance of tutors in the SKB in the Priangan region of West Java. Formulation of the problem in this research is how the influence of leadership style SKB, motivation, and work experience on performance. The hypothesis of this research is that there is influence between leadership style SKB, motivation, and work experience on performance. Study of theory in this research of which include the concept of Civil Learning For Educators Workforce Education Non-Formal Education (PTK-PNF), the concept of Performance, the head of the SKB concept leadership Style. Work Motivation concept, and the concept of Work Experience. The approach used is a quantitative approach with descriptive methods correlational analysis, as well as the study sample as many as 37 respondents.Based on the results of the study found that; 1) The influence of leadership style on performance SKB head tutors expressed with simple linear regression equation that shows a positive value, the greater the degree of correlation between the two variables is quite or moderate. 2) The effect of work motivation on the performance of tutors expressed with simple linear regression equation that shows a positive price, the degree of relationship between two variables classified as strong or tight. 3) The effect of work experience on the performance of tutors expressed with simple linear regression equation that shows a positive value, the greater the degree of correlation between the two variables is quite strong. 4) The effect of leadership style SKB, motivation and work experience expressed by multiple linear regression equation that shows a positive value, the greater the degree of relationship between variables is considered to be very strong or very closely. The conclusion of this study, namely, acceptance of the hypothesis that: 1) a significant difference between the style of leadership SKB on the performance of tutors with a large degree of relationship and considerable contribution, 2) a significant difference between the motivation to work on the performance of tutors with a large degree of relationship and a strong contribution, 3) there is a significant relationship between work experience on performance with a large degree of relationship and considerable contribution, 4) a significant difference between the style of leadership SKB, motivation and work experience on the performance of tutors with a large degree of relationship and contributed very closely.